Progressive tax reform in OECD countries: Perspectives and obstacles - Sarah Godar; Christoph Paetz; Achim Truger (International Labour Organization (ILO), 2014)
In most OECD countries the redistributive effect of the tax system has been substantially weakened by deliberate tax policies over the last decades. Despite some signs that this trend may have recently come to a halt a comprehensive policy change is not underway. One major argument brought forward against such a change is that of a serious trade-off between equity and efficiency: According to the dominant view higher taxes on top personal incomes, corporate income and wealth are detrimental to growth and employment. This paper argues that even the dominating theoreti cal framework leaves substantial leeway for redistributive taxation. From a Keynesian macroeconomic perspective redistribution may even be systematically conducive to growth and employment. Therefore, besides attempts at international tax coordination and harmonisation, national tax policies should actively use their room of manoeuvre for progressive taxation to correct the disparities in the income distribution and at the same time to increase the fiscal space.
Keywords: 330; tax reform; taxation; trend; OECD countries